Análisis de contenido en la plataforma digital de diario El Comercio sobre la violencia de género en tiempos de pandemia, marzo - agosto 2020 - Michelle Estefanía, Calderón Campaña (2022)
ABSTRACT: During the confinement and pandemic in Ecuador, according to Nydia Pesántez (2020), UN Women official Ecuador: 64% of women have suffered some sort of gender-based violence. 30% have happened inside their homes, 43% of cases, the perpetrator is the partner, boyfriend, husband. The likelihood of violence when the partner is at home or unemployed increases by 28%. With the above, the main objective of the research is to analyze the content on gender violence in times of pandemic in the publications of El Comercio Newspaper period March - August 2020, investigation used qualitative research where the ways of publishing the information are analyzed on the website and showing the data found in it. We analyzed the media treatment through functionalist theory as they emitted data. The emergence of new technologies has made traditional media evolve, having to adapt to new platforms such as the newspaper El Comercio, which had to create its website, where the research on gender-based violence was conducted based on the treatment of information and content, using content analysis matrices designed for the project. As a proposal, a scientific article was taken down with the results obtained from the research, which gotten off for publication in Iqual.Revista De Género E Igualdad Keywords: Gender violence, digital platform, daily business, content analysis.